2020
DOI: 10.21203/rs.3.rs-108405/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Satisfaction with nursing care and its related factors in patients with COVID-19: A Descriptive Correlational Study

Abstract: Background: Patients’ satisfaction is a fundamental factor in the quality of nursing care. The emergence of the novel coronavirus (COVID-19) and the highly contagious virus can affect nursing care by increasing the number of care-seekers. This study aimed to determine the patients’ satisfaction and related factors in patients with COVID-19 hospitalized in Taleghani Hospital, Urmia-Iran, in 2020. Methods: This descriptive correlational study was conducted on 196 patients with COVID-19 hospitalized in Taleghani … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
0
10
0
3
Order By: Relevance
“…The novel coronavirus outbreak was first identified in Wuhan, China, and it has now spread worldwide [ 16 ]. The current COVID-19 pandemic has increased anxiety and fear among the staff at the forefront of healthcare, especially nurses [ 17 , 18 ]. Studies in this area have shown that this disease affects nurses’ mental state, and therefore affects the quality of nursing care [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The novel coronavirus outbreak was first identified in Wuhan, China, and it has now spread worldwide [ 16 ]. The current COVID-19 pandemic has increased anxiety and fear among the staff at the forefront of healthcare, especially nurses [ 17 , 18 ]. Studies in this area have shown that this disease affects nurses’ mental state, and therefore affects the quality of nursing care [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This condition implies that the greater the patient's positive experience with hospital services, the more likely the patient will be satisfied with hospital services (Lemon & Verhoef, 2016; Asmaryadi er al., 2020; Sukawati, 2021). Professional care provided by health workers is also associated with the highest level of patient satisfaction, whereas patient education affects the lowest level of patient satisfaction (Parizad et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Educating patients about COVID-19 and potential drug reactions is crucial for nurses in ensuring the well-being of those under their care [17] , [18] , [19] , [20] , [21] , [22] , [23] . By providing clear and concise information, nurses empower patients to make informed decisions about their health.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of COVID-19, this education can include guidance on preventive measures, symptom recognition, and vaccination information [24] , [25] , [26] , [27] , [28] , [29] . Additionally, informing patients about potential drug reactions helps in managing their medications effectively and reduces the risk of adverse effects [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] . Through education, nurses play a pivotal role in promoting patient safety, enabling individuals to actively participate in their own healthcare, and fostering a sense of trust and confidence in the healthcare system [32] .…”
Section: Discussionmentioning
confidence: 99%